Peran Bahasa Indonesia dalam Meningkatkan Literasi Data Ekonomi: Studi pada Grafik Surplus Perdagangan Indonesia - Raffi Satrio Nugroho; Citra Auliya Pratiwi; Keisya Aliya Zasky Geovany; Raffi Satrio Nugroho; Natalia Desy Anggraeni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The low economic literacy of the Indonesian public is one of the main challenges in maximizing understanding of economic data, including trade surplus graphs. These graphs are often used to depict the performance of Indonesia's trade, but many people struggle to understand them due to the complexity of data presentation. As the national language, Indonesian plays a strategic role in bridging this understanding gap. This study aims to analyze how Indonesian can enhance the economic literacy of the public by simplifying and explaining trade surplus graphs. The method used in this study is a literature review, examining various official reports, academic publications, and trade surplus graphs released by government institutions such as the Central Statistics Agency (BPS). The analysis focuses on language structure, clarity of terms, and the narrative used to explain the graphs. The findings show that the use of simple and contextual Indonesian can help the public better understand economic data. Clear narratives, precise term selection, and simplification of information are key factors in improving the public’s economic literacy. By optimizing the role of Indonesian, the public can become more actively engaged in understanding the national economic situation and supporting better decision-making.